Recovery or Illusion? Assessing Corporate Performance and Investor Views in the Aftermath of Crisis - Resi Ariyasa Qadri; Maureen Novita Jawak (Pusat P2M Politeknik Negeri Batam, 2024)
This research is dedicated to examining the pre-and-post impact of the COVID-19 pandemic on the financial outcomes and market perceptions within the consumer goods industry, specifically focusing on the food and beverage segment. Employing a purposive sampling strategy for data collection and difference testing methods for analysis, this study adopts a quantitative approach to fulfill its objectives. The analysis incorporated a final sample comprising 15 companies within the food and beverage sector. Market perception was assessed using Tobin's Q ratio, while financial performance was evaluated through five distinct ratios. These ratios were subjected to an exhaustive examination utilizing both parametric and non-parametric difference tests. The empirical results reveal that, except for the debt ratio, which remained statistically unchanged, the other four ratios